Double Knockout Mutants of Arabidopsis Grown under Normal Conditions Reveal that the Plastidial Phosphorylase Isozyme Participates in Transitory Starch Metabolism. Issue 2 (3rd December 2013) - Malinova, Irina; Mahlow, Sebastian; Alseekh, Saleh; Orawetz, Tom; Fernie, Alisdair R.; Baumann, Otto; Steup, Martin; Fettke, Joerg
Abstract : A plastidial phosphorylase isozyme participates in starch metabolism and integrates with central carbon metabolism in the entire cell biology . Abstract: In leaves of two starch-related single-knockout lines lacking either the cytosolic transglucosidase (also designated as disproportionating enzyme 2, DPE2) or the maltose transporter (MEX1), the activity of the plastidial phosphorylase isozyme (PHS1) is increased. In both mutants, metabolism of starch-derived maltose is impaired but inhibition is effective at different subcellular sites. Two constitutive double knockout mutants were generated (designated as dpe2 - 1 × phs1a and mex1 × phs1b ) both lacking functional PHS1. They reveal that in normally grown plants, the plastidial phosphorylase isozyme participates in transitory starch degradation and that the central carbon metabolism is closely integrated into the entire cell biology. All plants were grown either under continuous illumination or in a light-dark regime. Both double mutants were compromised in growth and, compared with the single knockout plants, possess less average leaf starch when grown in a light-dark regime. Starch and chlorophyll contents decline with leaf age. As revealed by transmission electron microscopy, mesophyll cells degrade chloroplasts, but degradation is not observed in plants grown under continuous illumination. The two double mutants possess similar but not identical phenotypes. When grown in a light-dark regime, mesophyll chloroplasts of dpe2 - 1 × phs1a contain a single starch granule but under continuous illumination more granules per chloroplast are formed. The other double mutant synthesizes more granules under either growth condition. In continuous light, growth of both double mutants is similar to that of the parental single knockout lines. Metabolite profiles and oligoglucan patterns differ largely in the two double mutants.